Scaffolding Preservice Engineering Graphics and Design Teachers’ Interpretation Ability of Assembly Drawing (Nigerian Journal of Technology, 2021)
This study focuses on first-year Pre-service Engineering Graphics and Design teachers (PSEGDTs), as studies on the spatial-visual abilities of PSEGDTs is absent in mainstream spatial-visual literature. This paper reports on a teaching resource designed to support PSEDGTs' reading and interpreting AD. Data is presented in response to the following research questions, Does the comprehension of Assembly Drawing by PSEGDTs, alter after exposure to the teaching resource, if so how and, what contributed to the change? Twenty-one first-year PSEDGTs who participated in the authors' more extensive study were deliberately chosen to partake in this research. Individual interviews and focus group interviews were employed to develop data. Content analysis was embraced to elicit meaning from the data. The results highlight a significant improvement in most first-year PSEGDTs ability to read and interpret assembly drawings after the teaching resource. The research proposes an innovative strategy for teaching and learning of assembly drawing.